2020
DOI: 10.1037/aca0000250
|View full text |Cite
|
Sign up to set email alerts
|

Selection into, and academic benefits from, middle school dance elective courses among urban youth.

Abstract: Although research shows associations between adolescents general arts involvement and academic performance, little research documents links between enrollment in middle school dance elective courses and academic achievement, especially within low-income, urban populations. Further, differences between adolescents who do and do not have access to, or self-select into, middle school dance electives have yet to be identified. We prospectively followed a large (n ϭ 31,332), ethnically diverse sample of children fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…It is notable that the individual-level association was still present after adjustment for a range of demographic and socioeconomic covariates. Previous research has found strong associations between socioeconomic position, arts engagement 31 , and externalising behaviours 33 – 36 . Our findings align with the little longitudinal evidence available in this area and further support the theory that arts may be an effective risk reduction strategy 23 , 26 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is notable that the individual-level association was still present after adjustment for a range of demographic and socioeconomic covariates. Previous research has found strong associations between socioeconomic position, arts engagement 31 , and externalising behaviours 33 – 36 . Our findings align with the little longitudinal evidence available in this area and further support the theory that arts may be an effective risk reduction strategy 23 , 26 .…”
Section: Discussionmentioning
confidence: 93%
“…However, when children engage in the arts as part of extracurricular activities, arts engagement is socially and geographically patterned and linked with structural opportunities and barriers, with those from lower socioeconomic backgrounds less likely to engage with the arts 31 . Whilst this research has come from outside the US, concerns about unequal access to extracurricular arts activities has been voiced in the US too 32 – 36 . Schools therefore have an important role in providing universal access to the arts.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has not been a longitudinal, within-theater study of 21CS gains. While the field has mostly moved past issues with correlational designs being taken as definitive causal evidence (Goldstein et al, 2017; Winner et al, 2013), arts effects are rarely investigated over multiple years or levels within the same art form (Alegrado & Winsler, 2020; Gara & Winsler, 2019).…”
Section: The 21st Century Skillsmentioning
confidence: 99%
“…This study adds important new data on the benefits of arts participation in middle school, with implications for educational policy. Next, based on a large-scale prospective study that involved following an ethnically diverse sample of American children from preschool through 8th grade, Gara and Winsler (2020) were able to show that controlling for preexisting selection effects and prior academic achievement, dance engagement in middle school was associated with higher grade point averages and standardized test scores, better school attendance, and lower likelihood of suspension during middle school. From an educational policy perspective, this suggests that enrollment in middle school dance elective courses could benefit academic achievement, especially in low-income, urban populations.…”
Section: Thalia R Goldstein George Mason Universitymentioning
confidence: 99%